Guides or guidelines for interacting and playing with medical complex children: a qualitative documentary research - Jéssica Renata Bastos Depianti; Thaís Guilherme Pereira Pimentel; Fernanda Borges Pessanha; Juliana Rezende Montenegro Medeiros de Moraes; Ivone Evangelista Cabral (Universidade de São Paulo, 2024)
Objectives: to identify content on play and interaction with children with special health care needs recommended in clinical guidelines; analyze play and interaction activities applicable to children with special health care needs and complex care requirements. Method: qualitative documentary research based on guides, protocols, or guidelines on playing and interacting with children with special and living with complex care. Search terms in English (guidelines, playing OR play, complex needs, OR chronic disease) and in Portuguese ( guia, brincar ou brincadeiras, condições crônicas ) on the first ten pages of_Google Search ® . Thematic analysis was applied to the information extracted from the documents. Results: a total of nine documents with similar content were grouped into units of analysis, keeping only the interacting and playing activities applicable to children with special health care needs and living with complex care requirements, namely stimulation of potential, stimulation of adult-child interaction, and stimulation of the senses (touch, sight, and hearing), to be carried out by health professionals and family caregivers in the different care contexts. Conclusion: interaction and play are potential promoters of adult-child interaction, with application in the stimulating and life-delivering complex care for children.